Diretrizes de qualidade para a educação integral no Sistema Colégio Militar do Brasil - Lorenzoni, Adriana Roso (2020)
This dissertation, product of a research developed in the professional masters program in public policies and educational management, which is a part of the postgraduate program in public policies and educational management from the Federal University of Santa Maria, and the research and study group Gestar/CNPq/UFSM, approaches the theme of quality guidelines for all-round education in the Brazilian Military School System. It adheres to the research line Policies and Management of Basic and Higher Education and its general objective is “to understand which guidelines can contribute to qualify the all-round education in the Brazilian Military School System (BMSS)”. And, for specific objectives, it prioritizes: a) to recognize, in public educational policies, the principles, normative frameworks and programs/actions related to all-round education in Brazil; b) to comprehend the full-time school shift proposal, developed in the Brazilian Military School System, and its outspread in the schools part of said system; c) to outline dimensions and quality indicators for all-round education in the Brazilian Military School System. From the theoretical and methodological standpoint, the research bases itself on the qualitative approach, through the case study carried out in the Brazilian Military School System. As collaborators, it has the directors, the year coordinators and the pedagogical coordinators from the final basic education years of ten military schools that make up the System, using a mixed online questionnaire and document analysis. The theoretical framework, in particular, is supported by the studies of Moll (2012), Gadotti (2013), Libâneo (2012-2016), Cavaliere (2010-2014) and Dourado et al. (2013). The created product refers to an online portfolio containing guidelines for all-round education in the BMSS, which will be made available to the Education, Preparatory and Assistance Board of Directors, so that it can be socialized with the school units, with the expectation to promote studies, discussions and [re]articulations in Military Schools and a perspective to qualify the dynamics and support a substantial all-round education proposal. The motto of the study is the articulation of the full-time school shift in the BMSS schools. It was found that said full-time school shift was articulated in military schools under the assumption of all-round education, however, it constitutes as one of many complementary activities (literacy, numbering, tutoring, clubs, guilds, sporting and cultural activities, etc.) performed in after school hours, in a non-obligatory manner, on one day of the week. It is understood that these rich activities, listed in military schools as complementary, could be rearticulated to better contribute to the qualification of learning processes and the full formation of the students. In this perspective, a portfolio was produced with guidelines to support new articulations and conceptions about all-round education in the units of the Brazilian Military School System.